A label-free technique to quantify and visualize gold nanoparticle accumulation at the single-cell level - Wang, Chuan; Zhou, Hao-Ran; Zhao, Ya-Tong; Xiang, Zhi-Qian; Pan, Ke; Yang, Liuyan; Miao, Ai-Jun (Chemosphere (Oxford), 2022)
Despite their wide bioapplications, potential health risks of gold nanoparticles (AuNPs) remain unclear. As a determinant of their risks, AuNP accumulation within a cell population is subject to cell-to-cell heterogeneity. Methods to simultaneously quantify and visualize intracellular AuNPs at the single-cell level are, however, lacking. Here we developed a novel label-free technique, based on hyperspectral imaging with enhanced darkfield microscopy (HSI-DFM), to visualize and quantify AuNP accumulation at the single-cell level. The identification ability of the hyperspectral libraries derived from extra- and intracellular AuNPs was compared. The spectral number in the libraries was optimized to maximize their identification ability while minimizing the identification time. In addition, a filtration method was established to merge spectral libraries from different cell lines based on their similarity. The intracellularly accumulated AuNPs as determined by HSI-DFM well correlated with those detected by inductively coupled plasma mass spectrometry. This validation allowed us to calculate the intracellular concentration of AuNPs at the single-cell level and to monitor the accumulation kinetics of AuNPs in living cells. The label-free method developed herein can be applied to other types of AuNPs differing in their physicochemical properties as well as other NPs, as long as they are detectable by HSI-DFM. [Display omitted] •AuNP accumulation was visualized and quantified at the single-cell level.•Hyperspectral libraries derived from extra- and intracellular AuNPs were compared.•The spectral number in the libraries was optimized.•Spectral libraries from different cell lines were merged based on their similarity.•The quantification results of HSI-DFM well correlated with those of ICP-MS.